Мезоатомын гадаад Оже эффектийг бодох нэгэн арга - Kh, Tsookhuu; N, Tsogbadrakh (Scientific transaction of the National University of Mongolia. Physics, 2022)
A method for calculating mesic-atom external Auger transition is proposed. The transition proceed in two stages. In the first stage, the quasi-molecular complex, consisting of the mesic atom and the atom is formed in their collisions and on the second stage, the decay of this complex leads to external Auger effects. At given distance between two atoms of the quasi-molecular system, the partial and total width of external Auger transition are calculated. The average Auger transition rates of pionic helium (Helium gass pressure 59.44 atm, velocity of the pionic atom is v=105 cm/s) are calculated and compared the rates of other competitive processes (Internal Auger and Radiation transitions).